A Novel KISS1R Loss-of-function Variant in a Chinese Child with Congenital Hypogonadotropic Hypogonadism - Peng Zhou; Jin Wu (JCRPE, 2024)
Congenital hypogonadotropic hypogonadism (CHH) is a rare genetic disorder, resulting from impaired production, secretion, or action of gonadotropin-releasing hormone (GnRH). Variants of the KISS1R gene can result in CHH. Herein we describe a Chinese boy with CHH, caused by a novel, compound heterozygous variant in KISS1R. A male infant presented to the pediatric urological surgeon at three months of age for micropenis. Laboratory investigations done at this time revealed low levels of serum gonadotropins and testosterone, suggesting a lack of minipuberty. Topical application of dihydrotestosterone gel was recommended, but the parents refused treatment. The child was brought to our hospital at 3.3 years of age for the same complaint. A diagnosis of CHH was considered, and next generation sequencing revealed a compound heterozygous variant including a novel c.182C>A (p.S61*) and a c.418C>T (p.R140C) in KISS1R. We describe a novel compound heterozygous variant in the KISS1R in a boy with CHH, born to non-consanguineous Chinese parents. This report adds to the spectrum of variants in KISS1R seen in children with CHH.